Avaliação de sistemas de inventários sucessivos e dos interpoladores espaciais como instrumento de estratificação de povoamentos clonais de Eucalyptus sp. - Kanegae Júnior, Honório (2004)
This study analyzed 23 stands, predominantly, of Eucalyptus sp clones in successive measurements in the Continuous Forest Inventory-IFC, aiming at: analyzing the space dependence of dendrometric characteristics in 3 measurements, analyzing the efficiency of the use of the krigage and of the inverse of the distance as stratificator, in relation to simple random sampling and, based in the species control, age and spacing, defining the number of optimal strata for the stratification, based in spatial interpolators, evaluating the precision of IFC and of the sampling with partial replacement-ARP in stratified stands by the geostatistic krigage, defining the optimal proportion of permanent and temporary parcels and evaluating which spatial stratificator is the most efficient to be used by ARP. The results Showed that the dendrometric characteristics possess great variation in the degree of spatial dependence, varying from 0 to 100%, according to the project and the age of the stand analyzed , although more than 70% of the analyzed projects presented from average to strong spatial dependence for volume and 80% for the other variables; the reaches presented amplitude from 300 to 3.000 meters; the percentage of projects with strong spatial dependence decreases with the stand age, tending to the average spatial dependence, for all the analyzed variables; the decrease of the space continuity with time is the pattern that occurs more frequently, although it may increase in some projects and stand ages; the ARP presents use restrictions in stratified stands with less than 25 sampling parcels or 280 hectares of area; it is more efficient than IFC when 50% of the permanent parcels and 50% of temporary parcels are used, providing gain from 0 to 32% in the variance of the average, when compared with IFC; the efficiency of ARP increases with the measurement age and the stratification based on the krigage was superior to the stratification by the squared inverse of the distance in 49% of pairs of 1st and 2nd measurement, 32% of pairs of 2nd and 3rd measurement and 26% of pairs of 3rd and 4th measurement.